Incarceration and Health Care : A Visual Journey through the Lens of Activist Art - White, Tamara, (Arts, Creativities, and Learning Environments in Global Perspectives ;, 2025)
There is a lack of control that exists when managing a chronic illness, just as there is a lack of autonomy when one finds themselves living within the confines of a correctional facility. How does one address these two precarious circumstances when they collide? Research has revealed that incarcerated populations have a higher rate of infectious disease and chronic health issues than their non-incarcerated counterparts. How is this reality translated in a way that others might understand? As an avenue to gain a new perspective, this book provides a glimpse into the world of incarceration and health care management, using art to translate this experience. Activist art is effective and powerful for both the audience and the creator. By revealing the reality of living with a chronic illness and how social determinants of health significantly impact one's status and start in life, art holds the power to shift perspectives and deepen understandings not only of health care and incarceration but also to agitate for societal changes.